2018
DOI: 10.1038/s41598-018-21224-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct DNA and RNA detection from large volumes of whole human blood

Abstract: PCR inhibitors in clinical specimens negatively affect the sensitivity of diagnostic PCR and RT-PCR or may even cause false-negative results. To overcome PCR inhibition, increase the sensitivity of the assays and simplify the detection protocols, simple methods based on quantitative nested real-time PCR and RT-PCR were developed to detect exogenous DNA and RNA directly from large volumes of whole human blood (WHB). Thermus thermophilus (Tth) polymerase is resistant to several common PCR inhibitors and exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The direct RT-PCR in the application of DNA viral detection has shown promising results in hepatitis B and Mycoplasma organisms [ 21 , 22 ]. Other studies using direct RT-PCR on detecting viral RNA suggested that the use of PCR enhancers could lead to early RNAase release, which compromises the RNA integrity [ 23 ]. PCR inhibition is the leading cause of reporting low testing sensitivity in various fluids, in which some are reported as resistant to heat and demand the extraction step with sample dilution to eliminate the inhibition [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct RT-PCR in the application of DNA viral detection has shown promising results in hepatitis B and Mycoplasma organisms [ 21 , 22 ]. Other studies using direct RT-PCR on detecting viral RNA suggested that the use of PCR enhancers could lead to early RNAase release, which compromises the RNA integrity [ 23 ]. PCR inhibition is the leading cause of reporting low testing sensitivity in various fluids, in which some are reported as resistant to heat and demand the extraction step with sample dilution to eliminate the inhibition [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk for detection inhibition should be considered when analysing challenging samples such as those containing soil or blood. There are several studies where SYBR Green I detection has been applied for analysis of matrices that contain blood or humic acid [141][142][143], which may have skewed the results and conclusions. Using hydrolysis probes for detection is a much better alternative than dsDNA-binding dyes in order to avoid fluorescence inhibition when humic acid or haemoglobin is present in the reactions.…”
Section: Overcoming Fluorescence Inhibitionmentioning
confidence: 99%
“…There is controversy about the effect of heparin on the molecular assays. There are some reports implying that heparin, if not completely removed during extraction, can inhibit enzyme-based molecular tests (46,(60)(61)(62)(63)(64). It has been shown that even low concentrations of heparin may suppress DNA amplification although the inhibition of heparin on PCR using large amounts of DNA may be not significant (64)(65)(66).…”
Section: Whole Blood Plasma Serum Buffy Coat and Bone Marrowmentioning
confidence: 99%